CAREER ADMINISTRATION AS A DETERMINANT OF PROACTIVE BEHAVIOR - Azman Ismail; Wan Aishah Wan Mohd Nowalid; Azmawaty Mohamad Nor (Economic Review)
Career guidance and counselling and its numerous services are meant to address issues bordering on career development, social changes and challenges. One of the modern challenges and threats to effective functioning, productivity and efficient service delivery in organizations is rapid changes in the 21st century, which needs to be addressed headlong. By addressing the duo problem of organizational development and the human aspect of organization, career administration considers as expedient, having proactive individuals who assist in moving the organization forward. Proactive personality professionals achieve several desirable individual and organizational outcomes: objective career success, career satisfaction, job performance and organizational citizenship behavior, job satisfaction, affective commitment, taking charge and voice behavior which often are the central concern of every organization. This study examines the relationship between the career administration and proactive behavior. Self-report questionnaires are utilized to collect data from employees working at an oil and gas firm in West Malaysia. The results of SPSS program presented two essential outcomes: first, job autonomy was significantly correlated with proactive behaviour. Second, transformational leadership was significantly correlated with proactive behavior. This result demonstrates that career administration does act as an important determinant of proactive behavior in the studied organization. Additionally, discussion, implications and conclusion are elaborated.